Restructuring of MTB: factors that influencing the employees job satisfaction and organization commitment / Marliza Omar - Omar, Marliza (Faculty of Business and Management, 2006)
Recently, job satisfactions among the employee become the most crucial subject in implementing the organization progress. Due to that, this research is conduct to carry out the factors that influencing employees job satisfaction and commitment toward organization in respect of the restructuring of MTB. The restructuring of the company will affect the policies, procedures and culture will create stress for all the people involved. Since the employees will have to deal with new people, new procedure, possibly more work and loss of previous co-workers and friends, restructuring would implicit the employees job satisfaction and commitment